The Analyzing of Anonymous Trolling Comment On Social Media - fera Indasari; Siti Anisyah; Sepriadi Saputra (Universitas Islam Negeri Raden Fatah Palembang, 2024)
In this digital era, social media has become a space for interaction and communication for most people. However, behind its convenience and benefits, social media is also a place for negative behavior to emerge. One phenomenon of provocative comments on social media that often appears on social media platforms is trolling. This research aims to understand